2019
DOI: 10.24865/ajas.v4i1.141
|View full text |Cite
|
Sign up to set email alerts
|

A Written Grammatical Error Analysis of Second Year Students of Arabic

Abstract: Errors could likely be an integral part of the learning-teaching process. Writing errors of Arabic, in particular, are considered fundamental since they can act as significant data to determine the level of language proficiency, identify possible difficulties in student’s writing, and prepare further teaching aids and materials to meet students’ needs and problems. The objective of the current study, therefore, aimed to reveal the common types of errors and their frequencies committed by the students at Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Accordingly, Lado (1971) asserts if the linguistic feature differences between the first and the target languages are greater, the learning difficulties are expected to be higher. This might be supported by the study from Adila (2019) examining writing errors amongst Indonesian learners of Arabic. As grammatical rules in Bahasa Indonesia are mainly different from the Arabic ones, his findings show that interference of the mother tongue still became a major problem among other sources of errors.…”
Section: Interlanguage Errors Vs Intralingual and Developmental Errorsmentioning
confidence: 81%
See 1 more Smart Citation
“…Accordingly, Lado (1971) asserts if the linguistic feature differences between the first and the target languages are greater, the learning difficulties are expected to be higher. This might be supported by the study from Adila (2019) examining writing errors amongst Indonesian learners of Arabic. As grammatical rules in Bahasa Indonesia are mainly different from the Arabic ones, his findings show that interference of the mother tongue still became a major problem among other sources of errors.…”
Section: Interlanguage Errors Vs Intralingual and Developmental Errorsmentioning
confidence: 81%
“…Iḍāfa construction is categorized in two ways, namely simple iḍāfa and compound iḍāfa constructions (Adila, 2019) Last but not least, naʿt is linguistically an adjective, while according to the term, the meaning of naʿat, as mentioned in the book of Jurumiyah, is as follows:…”
Section: Error Of Phrases (Iḍāfa Jārr Wa Majrūr Naʿt Wa Manʿūt)mentioning
confidence: 99%
“…This misordering does not include a certain sub-type of error, but all types of errors that exist in students' instincts refer to this error (Imaniar, 2018). Adila (2019) explained that all these types of errors were the result of the learner's negligence in applying the rules of Arabic in writing sentences. The results of the error analysis on the tarkīb jumlah ismiyah in this student's insyā' indicate the need for stressing teaching materials, methods, strategies and appropriate media that can strengthen the understanding of the tarkīb rules, both in the context of simple sentences and more complex sentences.…”
Section: Zulaeha: Writing Composition Problem In Arabic Language Lear...mentioning
confidence: 99%
“…Zaid et al, (2019) reported that word and phrase errors in the form of substitution, addition and omission are also the biggest obstacles in learning Arabic. Adila (2019) and Khuwaileh and Shoumali (2000) argue that the most grammatical errors occur in the process of writing Arabic. Learners usually have difficulty in assembling fi'il and fa'il, as well as the compatibility between fi'il and time information.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies related with grammatical errors have been found in many papers. Some of the papers discussed the grammatical errors in students' writing (Adila, 2019); Fitria, Tira Nur, 2021); (Mohammed et al, 2015), speaking (Helmanda et al, 2018), and specifically past tense errors (Kartini, 2022). A study concerning with past tense errors in Soul Sense with Silkina Podcast seems not have been done yet.…”
Section: Introductionmentioning
confidence: 99%